2016
DOI: 10.1515/fv-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

Parasitofauna of Brown Bear (Ursus arctos) in the Protected Landscape Area CHKO — Poľana

Abstract: During the years 2015-2016 we obtained 15 samples of faeces of brown bears (Ursus arctos) and 2 samples of gastrointestinal (GI) tracts of young female brown bears for helminthological examinations. The samples of faeces were collected from various sites in the protected landscape area CHKO-Poľana, and the gastrointestinal tracts originated from bears hunted down in the same area within permitted regulation of bear population for 2015. Of the 17 samples collected from the CHKO-Poľana area, 13 were positive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…The prevalence of baylisascariasis in brown bears during the three years of our study was highest in autumn. Our findings are consistent with most studies that have investigated the seasonal dynamics of B. transfuga in bears [ 38 , 40 ]. These studies found that the prevalence was highest in autumn or winter and lowest in spring.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The prevalence of baylisascariasis in brown bears during the three years of our study was highest in autumn. Our findings are consistent with most studies that have investigated the seasonal dynamics of B. transfuga in bears [ 38 , 40 ]. These studies found that the prevalence was highest in autumn or winter and lowest in spring.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were reported by Major et al [ 38 ] in their coprological study, who also observed that the prevalence of B. transfuga was highest in autumn and winter and lowest in spring, which corresponds to the results of our study. Several studies have confirmed the occurrence of parasites in bears during the winter, when bears should hibernate [ 36 , 38 , 40 ].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations